Impact of Surgery in De Novo Metastatic Breast Cancer after Systemic Disease Control - Muhammad Muqaddas Mustafai, Abdul Manan, Muhammad Usama Hassan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Systemic chemotherapy is the standard of care for patients with metastatic breast cancer, with an undecided role in surgery. Limited data is available for the role of surgery on the overall survival of stage 4 breast cancer in regards to luminal subtypes of patients. This is a retrospective data analysis comparing overall survival benefit and disease-free survival in stage IV breast cancer after systemic treatment and systemic disease control concerning luminal classification in the last five years. Method: Patients who had surgery and no surgery after systemic treatment and disease control were compared for 5 years overall survival as the primary endpoint and disease-free survival as the secondary endpoint. The survival benefit was also compared in regards to tumor biology (ER/PR, HER2 status) Results: Data included 430 patients, 244 in surgery and 186 in no surgery group. At one year survival for surgery performed and not performed was not significant. Five-year overall survival for surgery performed and not performed was 84.4% and 74.6%. A statistically highly significant difference in survival rates was observed (p<0.0001). The mortality rate was 15.6% in surgery performed and 25.4% in the no-surgery group which showed a significant difference among the two study groups (p=0.011). We found statistically significant differences in luminal B (p=0.01) and triple-negative breast cancer patients (p=0.001) for survival rates in surgery performed and not performed groups. Conclusion: Surgery has a positive impact on overall survival in Stage 4 patients with systemic disease control even in high-risk luminal B, Her 2 Positive, and triple-negative breast cancer patients. There was no significant difference observed in disease-free survival who were operated on or not. However, there was no local recurrence in the operated group.